Development and Pilot-Testing of Key Questions to Identify Patients’ Difficulties in Medication Administration - Wurmbach VS (Dove Medical Press, 2021)
Viktoria S Wurmbach,1,2 Steffen J Schmidt,3 Anette Lampert,1,2 Simone Bernard,3 Christine K Faller,1,2 Petra A Thürmann,3,4 Walter E Haefeli,1,2 Hanna M Seidling1,2 On behalf of HIOPP-6 Consortium1Department of Clinical Pharmacology and Pharmacoepidemiology, Heidelberg University Hospital, Heidelberg, Germany; 2Cooperation Unit Clinical Pharmacy, Heidelberg University Hospital, Heidelberg, Germany; 3Department of Clinical Pharmacology, School of Medicine, Faculty of Health, Witten/Herdecke University, Witten, Germany; 4Philipp Klee-Institute for Clinical Pharmacology, HELIOS University Clinic Wuppertal, Wuppertal, GermanyCorrespondence: Hanna M SeidlingHeidelberg University Hospital, Department of Clinical Pharmacology and Pharmacoepidemiology, Im Neuenheimer Feld 410, Heidelberg, 69120, GermanyTel +49 6221/56-38736Email hanna.seidling@med.uni-heidelberg.dePurpose: The development and testing of key questions suitable to identify patients’ difficulties with medication administration.Materials and Methods: We used a consecutive five-step process to draft key questions regarding 43 aspects of medication administration that can be difficult for patients who manage a complex drug treatment: Step 1) Identification of potentially error-prone characteristics of drug treatment (such as certain dosage forms) and initial draft of key questions. Step 2) Assessment of how comprehensible the questions are for patients. Step 3) Pre-testing of exemplary key questions with patients and monitoring of patient’s actual medication administration behavior. Step 4) Evaluation by general practitioners of how well the questions may be integrated into actual patient visits. Step 5) Final approval of the questions in an expert panel. Thereafter, we pilot-tested exemplary questions with 36 patients (43 tests). In the course of this pilot-testing, the patients’ answers to the key questions were tested against both their actual behavior during medication administration and against their answers to more general questions regarding potential difficulties with medication administration.Results: More than half of the key questions (N = 24/43) were revised at least once during the development process. During the pilot-testing, 55.8% of the pilot-tests (N = 24/43) revealed medication administration difficulties. It was observed that the key questions identified significantly more difficulties (N = 17) than the general questions (N = 8; P = 0.021, positive predictive value = 94.4% vs 88.9%). In one case, both a key question and a general question identified difficulties, which, however, was not confirmed during the drug administration demonstration, indicating a false positive rate of 5.3% in both cases.Conclusion: We developed key questions aimed at detecting administration errors with a high specificity and a significantly higher sensitivity than general questions, suggesting that the resource-intensive demonstration of medication administration can be reserved for the detection of rarer and uncommon administration errors.Keywords: medication adherence, medication errors, quality of health care, patient preference